Konsep Ramah Lingkungan pada Penataan Permukiman Kumuh di Kota Lhokseumawe Provinsi Aceh (Studi Kasus: Pusong Lama) - Angela Prastica; Sitti Zubaidah; Romaynoor Ismy (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The high population growth in Lhokseumawe City has resulted in increasingly limited residential land with poor and uninhabitable infrastructure, resulting in the formation of slum settlements in the Pusong Lama area, Banda Sakti District, which have various problems such as irregular buildings, damaged roads, and drinking water is not available, drainage is damaged, waste water management is not available, waste management is not available and fire protection is not available. The aim of this research is to analyze the level of slums and analyze the arrangement with an environmentally friendly concept. Data collection was carried out through the process of observation and interviews. The scoring process is carried out by giving a weight score of 5, 3 or 1 to each slum criterion to get a percentage result. The research results show that the level of slums is in the light slum category. Implementing SPALD, waste isolation and composting equipment, biopores, implementing the 3R integrated waste management system and eco-drainage are environmentally friendly planning solutions.